Determination of hydroquinone using poly(3‐methylthiophene) synthesized electrochemically on pt electrode in methylene chloride. Issue 19 (5th May 2014) - Kavanoz, Muammer; Bük, Ufuk; Ülker, Emine
ABSTRACT Poly(3‐methylthiophene) (P3MT) film was synthesized by potentiodynamic method on Pt electrode in methylene chloride solution containing 0.10M tetrabuthlammonium perchlorate supporting electrolyte and used for the determination of hydroquinone (HQ) with amperometric I–t method in solution consisting of NaHSO4/Na2SO4 (SBS; pH 2.0). This modified electrode has a lower working potential and good operational stability due to reducing electrode fouling when compared with the direct oxidation of HQ at the bare Pt electrode. Limit of detection, limit of quantification, and the linear response range were found to be 1.32 × 10−5 mM, 4.41 × 10−5 mM, and between 4.41 × 10−5 – 50.0 mM (R2 = 0.997), at 0.50 V versus saturated calomel electrode, respectively. HQ determination in complex matrix was checked using real samples to demonstrate the applicability of modified electrode. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40859.